Agriculture Sectors and Its Contribution to National Economy in Nepal - Dhakal, Chandra Prasad (Nepal Journal of Multidisciplinary Research, 2022)
Agriculture is one of the main economic sectors of Nepal that play important role for economic enhancement. In 2020/21 agriculture sectors including fisheries and livestock occupy the around 25 percent in national GDP which was around 32 percent in 2011/12. Contribution of agriculture sectors is decreasing in national GDP; however, the role of agriculture sectors is very important in national production and poverty alleviation. The study analyzes the contribution of agriculture sectors in national GDP through highlighting the data of per unit production of agriculture products and gives suggestions for its enhancement in national GDP. To complete the study, it has been followed both qualitative and quantitative research design. The study is based on secondary source of data and the data were collected through library and internet research. Conclusion of the study was based on data analysis and presentation.